2021
DOI: 10.1155/2021/6627562
|View full text |Cite|
|
Sign up to set email alerts
|

A Nomogram Predicting the Prognosis of Renal Cell Carcinoma Patients with Lung Metastases

Abstract: Background. The optimal tool for predicting the survival of renal cell carcinoma (RCC) patients with lung metastases remains controversial. Methods. We selected patients diagnosed with RCC and lung metastases, from 2010 to 2015, from the Surveillance, Epidemiology, and End Results (SEER) database. After the selection of inclusion criteria and exclusion criterion, the rest of the patients were incorporated into model analysis. Least absolute shrinkage and selection operator (LASSO) regression was used to select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…Although the treatment of mRCC has made progress in the past two decades, the prognosis of patients with mRCC remains dismal ( 15 ). Previous studies on mRCC generally concentrated on the long-term survival of patients ( 16 , 17 ) or risk factors related to lung and bone metastasis ( 18 , 19 ). However, advanced or highly invasive tumors often lead to early death and few study has identified risk factors associated with early death in mRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Although the treatment of mRCC has made progress in the past two decades, the prognosis of patients with mRCC remains dismal ( 15 ). Previous studies on mRCC generally concentrated on the long-term survival of patients ( 16 , 17 ) or risk factors related to lung and bone metastasis ( 18 , 19 ). However, advanced or highly invasive tumors often lead to early death and few study has identified risk factors associated with early death in mRCC.…”
Section: Discussionmentioning
confidence: 99%
“…9 variables with nonzero coefficients were selected by optimal lambda. 6 Journal of Oncology cell carcinoma [20]. ese risk factors were also important in other distant metastases of kidney cancer [1,7].…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have reported some biomarkers other than the above predictors for LM prediction [26], few of these markers have been applied. Previously, Xinyu Sheng's team at the Zhejiang University School predicted LM in kidney cancer patients based on patient data from the SEER database, with a column line plot of development and a model constructed based on TNM stages with ground AUC of 0.780 and 0.618, respectively, and the study was not externally validated [20,27]. Although the AUC of the models developed in the training set is greater than 0.50, there is still room for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The nomograms prediction model represented by UISS (9), SSIGN (10), Leibovich (11) was born and provided treatment suggestions for clinicians. In terms of the RCC transfer prediction model, we found that the prediction models for each leading transfer site of RCC were reported (12)(13)(14), but the C-index of the model was 0.714-0.803, and the area under the curve (AUC) was 0.767-0.780, indicating that the relative accuracy was insufficient. And the distant metastasis prediction model for the overall large sample of the elderly has not been reported.…”
Section: Introductionmentioning
confidence: 99%